Biology Reproduction aspects study of Yellowtail Fusilier (Caesio sp.) Landed at Ternate Archipelago Fishing Port, Indonesia - Irham, Irham; Susanto, Adi Noman; Iksan, Kusdi Hi.; Ahmad, Aditiyawan; Karim, Wanty Julianti; Alhadad, M. Said (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research aims to determine growth patterns, gonad maturity levels, gonad maturity index and size of first mature gonads. The research was carried out for 5 months starting from November 2023 to March 2024 with the sampling location at PPN Ternate. Data collection used the observation method (direct observation). The data was analyzed using Microsoft Excel. The results of the sex ratio for male and female escaped fish were 1: 1.36, indicating that the catch of fish was balanced at 1: 1. The results of the analysis of the relationship between length and weight showed that male and female escaped fish were allometrically negative, where there was a faster growth in length than weight gain. The level of gonad maturity in the yellowtail (Caesio sp.) (males and females) experienced the highest gonad maturity in March with the number of mature gonads in male fish amounting to 46,49% and the number of mature gonad in fish amounting to 54,04%. The hight gonad maturity indeks value in male and female escaped fish occurred in March. Based on analysis of the gonad maturity indeks (IKG), the fish with the highest TKG was found in TKG IV with a value of 1,8526. the avarage size of mature gonads for male fisht is 252 mm and famale fish is 243 mm.